Luminescent Bimetallic d-f Complexes - Cameron, Lee John (Curtin University, 2024)
This thesis reports the synthesis and characterisation of novel luminescent iridium-lanthanide complexes. The resulting compounds were analysed using single crystal x-ray diffraction and various spectroscopic techniques to improve our understanding of the mechanisms that enable the emission of light.